Cognitive psychology and tourism - Scott, Noel; Moyle, Brent; Campos, Ana Cláudia; Skavronskaya, Liubov; Liu, Biqiang (Emerald Publishing Limited, 2023)
Compiled from 10 years of research, with chapters contributed by experts in the field, we demonstrate how tourism will benefit from applying a new paradigm found in mainstream psychology, termed here the 'Cognitive Wave'. Tourism professionals who apply this will benefit by identifying how they apply concepts such as attention, emotion, sensations, and memory in their work, and critically understand how to measure them. The work is arranged into five sections. Chapter 1 introduces the 'Cognitive Wave' and discusses the potential advantages and disadvantages. Chapter 2 introduces the mental processes central to cognition. Chapters 4 and 5 provide examples of disambiguation, translating tourism concepts and theories into those of cognitive psychology. Every chapter highlights relevant existing research and opportunities for further developments. Real-world examples of the application of theory and methods to tourism, hospitality, events, leisure, and service fields are provided. There are many opportunities for developing these, and other topics, further and in developing the work of the invisible college which underpins the silent shift to the 'Cognitive Wave'.
Keywords: Tourism -- Psychological aspects.; Cognitive psychology.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality, Travel and Tourism law.; Hospitality, sports, leisure and tourism industries.; elektronické knihy; electronic books